Xanthones and xanthone derivatives from Garcinia nitida - Ee, Gwendoline Cheng Lian; Lim, Che Kiong; Yap, Taufiq Yun Hin; Md. Sukari, Mohd Aspollah; Rahmani, Mawardi (Universiti Putra Malaysia Press, 2007)
A detiled chemical study on the stem bark extracts of Garcinia nitida has led to the isolation of five xanthones and two triterpenoids. They are 1,3,7-trihydroxy-2,4-bis(3-menthylbut-2-enyl)xanthone (1) osajaxanthore, (2) inophylin B, (3) 3-isomangostin, (4) rubraxanthone, (5) stigmasterol and stigmasterol acetate. The structures of these compounds were established using mainly 1D and 2D NMR spectrocopy. Acetylation of rubraxanthone resulted in two new compounds, rubraxanthone monoacetate (6) and rubraxanthone diacetate (7) with rubraxanthone triacetate (8).